Metacognitive Therapy for Depression Reduces Interpersonal Problems: Results From a Randomized Controlled Trial - Strand, Eivind R.; Hagen, Roger; Hjemdal, Odin; Kennair, Leif E. O.; Solem, Stian (Frontiers in Psychology, 2018)
Interpersonal problems are significantly elevated in patients with depression. Metacognitive therapy (MCT) for depression does not address interpersonal problems, but is associated with large reduction in depressive symptoms. The main aim of the current study was to explore whether MCT leads to improvements in interpersonal problems in patients with depression. The study was a waitlist controlled trial and assessments took place at pre- and post-treatment as well as 6-month follow-up. At pre-treatment, the sample had more interpersonal problems compared to samples from other studies of psychiatric outpatients. MCT was associated with large reductions in interpersonal problems. Level of interpersonal problems were not related to poorer treatment response. MCT, which does not directly target interpersonal problems, worked well for patients with depression and interpersonal problems. Future research should compare MCT with other evidence-based treatments for patients with depression and interpersonal problems.